2019
DOI: 10.1021/acsabm.9b00092
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial, Microparticle-Based Delivery of Immune Modulators Reprograms the Dendritic Cell Phenotype and Promotes Remission of Collagen-Induced Arthritis in Mice

Abstract: Safe, effective, antigen-specific therapy for rheumatoid arthritis (RA) remains an elusive clinical goal with a few lasting, viable options on the horizon. Existing therapeutic interventions are indiscriminate and inconsistently immunosuppressive, often leaving patients susceptible to infection. Herein, we investigate the use of a dual-sized, microparticle “regulatory vaccine” (REGvac) that passively targets dendritic cells for antigen-specific biomaterial-based immunotherapy of RA. This REGvac employs poly­(d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 67 publications
2
36
0
Order By: Relevance
“…In addition to development of vaccines, engineering the immune system also involves mimicking cellular and molecular mechanisms present in the immune system. For example, biomaterials can be utilized to mimic immune cells by delivering proteins and small molecules [ 188–193 ] and affect the overall outcome of the disease. Moreover, immune engineering also involves delivery of cells shielded from the immune system for affecting the outcome of different diseases and disorders.…”
Section: Future Outlook: Application Of Cofs In Immune Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to development of vaccines, engineering the immune system also involves mimicking cellular and molecular mechanisms present in the immune system. For example, biomaterials can be utilized to mimic immune cells by delivering proteins and small molecules [ 188–193 ] and affect the overall outcome of the disease. Moreover, immune engineering also involves delivery of cells shielded from the immune system for affecting the outcome of different diseases and disorders.…”
Section: Future Outlook: Application Of Cofs In Immune Engineeringmentioning
confidence: 99%
“…[ 191 ] Using a microparticle capable of delivering multiple immunosuppressive molecules, it was demonstrated that inflammation in a rheumatoid arthritis mouse model can be decreased. [ 190 ] Similar to the cancer treatments previously described, COFs with the ability to load large payload can also be used to deliver and target specific pathways via drug delivery approaches for preventing inflammation.…”
Section: Future Outlook: Application Of Cofs In Immune Engineeringmentioning
confidence: 99%
“…The incorporation of biomaterials into drug design, or rather drug delivery technology, blunts conventional drug limitations, permitting augmentations in a myriad of ways. Biomaterials are any materials not considered food or drugs that come into contact with tissue [76] and are being routinely investigated in many therapeutic applications including cardiovascular disease [77], neurodegenerative disease [78], cancer [79], vaccines [80], and autoimmunity [81][82][83]. Using biomaterials to engineer drug delivery systems across different scales offers numerous advantages.…”
Section: Biomaterial-based Immunotherapies For Ramentioning
confidence: 99%
“…Microparticles can also act to provide safe intracellular delivery of a broad range of biological agents including peptides and nucleic acids [84]. As such, design of novel NPs and MPs is being heavily investigated to specifically alter aberrant immune cell behavior to treat various immune-dysregulated maladies [82][83][84]. Unsurprisingly, researchers have begun investigating the use of biomaterial-based systems to treat RA, given its pathogenesis being highly immune cell-driven [81].…”
Section: Biomaterial-based Immunotherapies For Ramentioning
confidence: 99%
“…The generation and delivery of mixed particle co-assemblies has been explored to improve the biodistribution and tissue retention of drug carriers and to deliver multiple cargo types with © 2020 Wiley-VCH GmbH independent release rates. [11,45,46] However, the generation of injectable mixed colloidal assemblies with controlled particle suspension dynamics remains a challenge. Based on our results developing MIN6-HARP cellular suspensions, we hypothesized that HARPs could serve as colloidal scaffolds to improve the suspension dynamics of mixed particle systems through HARP network formation and electrostatic interactions between positively charged chit-HARPs and negatively charged microspheres.…”
Section: High Aspect Ratio Particles As Scaffolds For Colloidal Co-assembliesmentioning
confidence: 99%